Change of soil properties and microbiological activity under the vegetation of pastures - Nabieva, Gulchekhra (Biological Communications, 2016)
Most of the territory of the Navoiy province of Nurata region is occupied by the degraded pastures which are the main source of food supply of animal husbandry. This paper is devoted to investigation of agrochemical and microbiological properties of soils of pastures under agrophytocenosis of 1986, 1996, 2012 and under natural pastures of the study area. It is revealed that improvement of biological, agrochemical properties of the studied soils, depends on duration of the period of use of the land in the pasture regime. Features of biological parameters of the degraded soils depending on their prescription of use and type of plants, humus content agrochemical properties are revealed. If the activity of pasture plants during 3–19–29 became a permanent factor pasturable plants (zhitnyak — Agropyron desertorum L., chagan — Halothanus subaphyllus, astragal — Astragalus agameticus Lipsky) improve soil properties and increase microbiological activity of light gray agricultural soils. Refs 20. Figs 3. Table 1.